Total burn care - Herndon, David N. (Saunders Elsevier, 2012)
Total Burn Care guides you in providing optimal burn care and maximizing recovery, from resuscitation through reconstruction to rehabilitation! Using an integrated, "team" approach, leading authority David N. Herndon, MD, FACS helps you meet the clinical, physical, psychological, and social needs of every patient. With Total Burn Care, you'll offer effective burn management every step of the way.